Quality Criteria For E-Learning Courses - Morze, H.B.; Glazunova О Г. (Journal of Information Technologies in Education (ITE), 2009)
The author examines problems of estimation of quality e-learning courses that are designed for platform-based distance learning in the context of the requirements of the Bologna convention and cast the main criteria that should satisfy a course.